Cellular sequestrases maintain basal Hsp70 capacity ensuring balanced proteostasis - Ho, Chi-Ting; Jawed, Areeb; Zahn, Regina; Bukau, Bernd; Mogk, Axel (Nature Communications, 2019)
The sequestration of misfolded proteins into large assemblies by sequestrases is now considered as the third pillar in protein quality control besides chaperones and proteases. Here the authors characterise the functions of the sequestrases Hsp42 and Btn2 in the proteostasis network of S. cerevisiae and find that they protect cells from too exhaustive depletion of the Hsp70 system.
Gesehen am 03.04.2020